Neighbourhood-level analysis of the socio-spatial context of business crime in Northern Ireland - Ojo, Adegbola 19XX- (Crime prevention and community safety, 2021)
The repercussions of crime on businesses can be very significant. It can deter investment and frustrate business growth. Crimes result in higher costs of doing business because of the need to deploy multiple security measures. Business crime also leads to loss of output, for instance due to reduced hours of operation and depletion of morale of staff. Using a spatial segmentation analytical framework, this research study models the neighbourhood patterns of crimes perpetrated against small business in Northern Ireland. The study also accounts for the levels of non-reporting of crime victimisation among business owners together with the factors influencing the non-reporting of crime. Results show that indeed businesses within certain neighbourhood types are disproportionately exposed to crime. We also find evidence that multiple business owners have adopted crime prevention measures without considering what works in preventing business crime in the specific types of neighbourhoods within which their enterprises are located.